(untitled) (The Pakistan Development Review, 1976)
Poultry raising on scientific and commercial lines is relatively new to Pakistan, indeed, to this whole of the Sub-continent. In undivided India village farmers used to keep some fowls which were produced on primitive methods of natural hatching under the broody hen and reared on garbage dumps, left¬over meals, and mixed grain, which involved almost no financial investment. No special care was taken to prepare poultry feed or arrange for poultry health and hygiene. The basic idea of such part-time farming was to augment one’s income from the sale of eggs and birds. This part-time farming still accounts for about 85 percent; of Pakistan’s total egg production.1 To match the tremendous rise in demand for meat growth in poultry farming will have to take place on more modern and capital-intensive chicken farms. Such enterprises are the subject of this study.